Pengembangan Kreativitas Anak Kelompok B Melalui Teknik Gradasi Mewarnai di RA. Wardatul Muna Madiun - Rahmawati, Alvi Dyah; Fadhilla, Fajar (Absorbent Mind: Journal of Psychology and Child Development, 2021)
Early childhood education is a period of guidance in shaping physical and spiritual development. In this Jenajang children are not only given learning experiences, but children are given guidance in optimizing their brain development. Childhood also has an important influence on the development of children's creativity. Children's creativity talents need to be nurtured from an early age to determine the next child's experience. This research was conducted using a descriptive approach to the type of case study research. The source of this data consisted of respondents consisting of B grade students and the information was the head of the RA and the supervising teacher. The data in this research were obtained from observation, interviews and documentation. From the results, it was found that the use of the gradient method in coloring activities includes several stages, namely, a) introduction of basic colors, b) recognition of one color, c) recognition of two colors without being mixed, d) recognition of three colors without being mixed, e) introduction of gradation techniques from dark to light, f) Introduction of light to dark gadasi technique. Meanwhile, the development of children's creativity through coloring pictures with gradation techniques at RA Wardatul Muna as follows, a) Bringing a coloring art teacher to school, and b) Involving children in coloring competitions